Geography in the students vision of the world: reports of a methodological experimentation in teaching in São Luís, Maranhão - Celeri, Marcio José; Oliveira, João Gabriel da Silva (Geosaberes; Vol 9 No 17 (2018): Jan - Apr, 2017)
The present work deals with a methodological experimentation on the teaching of school geography with students from the second year of high school in a state school system in. Through the geographic knowledge built through the lived space of the students. The work was carried out at the Barjonas Lobão school by undergraduates of the degree course in Geography of the Federal University of Maranhão in the year 2017 and had the objective of approaching the students with the school reality. This contact resulted in the production of maps, through social cartography, where the students represented their realities. It was concluded that the students have preference for classes that flee from the traditional methodology and that can help to understand and to act in their daily life.
Keywords: Geografia Escolar; Metodologias de Ensino; Cartografia Social; Experimentação de Ensino.